PENGELOLAAN PEMBELAJARAN EKONOMI BERBASIS IT KELAS XII Dl SMAN 1 GETASAN - Ariyanti, Ariyanti; Markhamah, Markhamah; Syamsudin, Syamsudin (Jurnal Penelitian Humaniora, 2012)
The purpose of this study was to describe the material, instructional strategy, media, and interaction of IT-Based Economic Learning for Class XII at SMAN 1 Getasan. It was a qualitative study using ethnographic design. Data collection method used was in depth interview, observation, and documentation. Data analysis technique used was analysis arranged in site. Data validity test used was credibility and confirmability.The findings suggested that the Economic subject materials taught at SMAN 1 Getasan were from Economic textbook published by Yudistira, Students worksheets, and also other references such as internet. Strategies of IT-Based Economic Learning at SMAN 1Â Getasan focused not only on the use of technology but also on the principle of active students. lnstructional media of IT-based economic learning at SMAN 1 Getasan wasÂ very practical as presented in electronic form via LCD or player. Media used were macromedia flash software. There were one-way and two-way interactions in it. Oneway interaction occurred when teachers delivered material required an understanding while students were asked to pay attention. Two-way interactions were visible in all teachers and students activities in question and answer sessions, study group activities, and discussion.